Student Response about the Mini Lecture (Cermin) Learning Program Relationship with Student's Learning Intensity in the Field of Islamic Religious Education - Santi Rahayu (Interdisciplinary Social Studies, 2021)
In the current era of globalization, education is very important. If the education of a society develops well, then it is undeniable that the community will be more "qualified" and able to compete against competition that is getting tighter and tighter in various aspects of life activities. In such situations and conditions, "quality" human resources can face competition in life activities. This study aims to find out student responses about Mini Lectures (Mirror) by class II Mekar Arum High School Bandung, knowing the learning intensity of class II SMA Mekar Arum Bandung in the field of Islamic Education studies, and knowing the relationship between class II responses to lectures Mini (Cemrin) with the intensity of their learning in the field of study of Islamic Education. This study used a qualitative approach. The method used was descriptive. The data collection implemented was library research. The object being researched, as well as the data source, was the book Ta'alim Muta'alim by Syaikh Burhanuddin Az-Zarnuzi. The data collection method uses descriptive methods and the author performed content analysis. The results showed that students' etiquette towards teachers are students must always respect the teacher and the teacher's family, protect the rights of the teacher, do not walk in front of the teacher, do not sit in the teacher's place, do not start a conversation without the teacher’s permission, do not ask something when the teacher is bored, be on time, do not knock on the door of the teacher's house but be patient waiting for the teacher to come out